2021
DOI: 10.36416/1806-3756/e20210281
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and vitamin D in Brazilian adolescents: Study of Cardiovascular Risks in Adolescents (ERICA)

Abstract: Objective: To evaluate the association between asthma prevalence and serum levels of vitamin D in Brazilian adolescents. Methods: This was a cross-sectional, school-based study involving adolescents between 12-17 years of age from four large Brazilian cities located at different latitudes (Fortaleza, Rio de Janeiro, Brasília, and Porto Alegre). Information on asthma diagnosis, lifestyle, and sociodemographic characteristics was collected by means of self-administered questionnaires. Serum concentrations of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…10 Similarly, we found stronger associations between metabolic alterations, such as increased BMI and severe asthma. 9 On the other hand, we found no significant associations between active or severe asthma and hypovitaminosis D. 12 PeNSE assessed aspects other than prevalence related to asthma in Brazilian adolescents. One study looked at socioeconomic, environmental, psychosocial, family-related and lifestyle factors associated with asthma in Brazilian adolescents.…”
Section: Figurementioning
confidence: 51%
See 4 more Smart Citations
“…10 Similarly, we found stronger associations between metabolic alterations, such as increased BMI and severe asthma. 9 On the other hand, we found no significant associations between active or severe asthma and hypovitaminosis D. 12 PeNSE assessed aspects other than prevalence related to asthma in Brazilian adolescents. One study looked at socioeconomic, environmental, psychosocial, family-related and lifestyle factors associated with asthma in Brazilian adolescents.…”
Section: Figurementioning
confidence: 51%
“…11 On the other hand, it was not associated with serum vitamin D levels. 12 In relation to metabolic parameters, it was observed that MS and some of its components, such as WC, were significantly associated with severe asthma in Brazilian adolescents. 9 ISAAC was one of the key global studies designed to investigate the epidemiology of asthma in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations